BeagleBone essentials : harness the power of the BeagleBone Black to manage external environments using C, Bash, and Python/PHP programming /: harness the power of the BeagleBone Black to manage external environments using C, Bash, and Python/PHP programming. (2015) - Giometti, Rodolfo
No abstract available